Introduction to Dossier. Popular Economies: Between informality and social reproduction - Gago, Verónica; Cielo, Cristina; Gachet, Francisco (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2018)
Introduction to dossier "Popular Economies: Between informality and social reproduction"